The Role of Sirtuins in Cell Life and their Potential Therapeutic Uses - Caballero-Méndez, Lyda C.; García, Andrea E.; Franco-Montoya, Luz Natalia (Puerto Rico Health Sciences Journal, 2023)
Sirtuins (SIRTs) constitute a family of enzyme-type proteins dependent on nicotinamide adenine dinucleotide. These enzymes are considered cellular metabolic sensors since the cell’s energy level can regulate their activity to compensate for energy fluctuations. They constitute an evolutionarily conserved family of deacetylases class III enzymes, with a recognized role in prolonging life expectancy. Sirtuins are related to the development of age-associated pathologies, such as cancer, diabetes, neurodegeneration, and metabolic disorders. This group of enzymes has become a possible therapeutic target due to their capacity for modulating cellular processes, such as genome repair and maintenance, and for regulating metabolic pathways, homeostasis, and cell proliferation. In addition, SIRTs are associated with pathologies such as cancer and COVID-19. There is a need for future studies that will clarify the relationship between these enzymes group and the prevention and development of diseases.